Fiscal consolidation after COVID-19: Issues and policy options in sub-Saharan Africa - Vedanth Nair; David Phillips; Daniel Prinz; Ross Warwick (Institute for Fiscal Studies (IFS), 2021)
The COVID-19 pandemic has hit sub-Saharan African economies hard, exacerbating debt and debt servicing cost issues that a range of countries in the region - including Ghana and Nigeria - already faced. This report examines the fiscal context in sub-Saharan Africa and the issues and options for potential post-COVID-19 fiscal consolidation efforts. Since Spring 2020, the COVID-19 pandemic has had significant impacts on the public finances of both developed and developing countries. Falls in revenues and increases in public expenditure have pushed up deficits and debts, posing a particular challenge for many countries in sub-Saharan Africa (SSA). After the debt relief of the 2000s, the 2010s saw public debt and debt-servicing costs grow substantially across the region, with the fiscal situation looking increasingly unsustainable in some countries even prior to the pandemic. This difficult context may be one reason why the scale of discretionary tax and spending policy measures undertaken in response to the pandemic has generally been much smaller than in high-income countries. This report sets out the trends and forecasts for budget deficits, debts and debt-servicing costs in SSA, and provides an overview of the issues and options for potential post-COVID-19 fiscal consolidation efforts.
Keywords: 330; Haushaltskonsolidierung; Öffentliche Schulden; Finanzpolitik; Coronavirus; Subsahara-Afrika